Dielectric, ferroelectric and electric field-induced strain behavior of Ba(Ti0.90Sn0.10)O3-modified Bi0.5(Na0.80K0.20)0.5TiO3lead-free piezoelectrics - Pharatree Jaita (2018)
Lead-free piezoelectric ceramics of (1 - x)Bi 0.5 (Na 0.80 K 0.20 ) 0.5 TiO 3 -xBa(Ti 0.90 Sn 0.10 )O 3 or (1 - x)BNKT-xBTS (when x = 0-0.20 mol fraction) were investigated. Optimum sintering temperature was found to be 1125 C at which all compositions had relative densities 98-99% of their theoretical values. All compositions exhibited a single perovskite structure. The unit cell size expansion was observed as BTS content increased. A slight reduction of grain size was noticeable when small amount of BTS was added. The BNKT-0.05BTS sample had a large electric field-induced strain (S max ) of 0.36% which corresponded to the normalized strain coefficient (d33â̂ -) of 649 pm/V. The highest piezoelectric coefficient (d 33 = 215 pC/N) with good dielectric (É r = 1721, tan δ = 0.0724 and T c = 333 C) and ferroelectric properties (P r = 20.49 μC/cm 2 , R sq = 0.87) were obtained for BNKT-0.10BTS sample, suggesting that this composition had a potential to be one of the promising lead-free piezoelectric candidates for further use in actual applications. © 2014 Elsevier B.V. All rights reserved.